2014
DOI: 10.1016/j.forsciint.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Post-mortem genetic analysis in juvenile cases of sudden cardiac death

Abstract: Background: The reason behind a sudden death of a young individual remains unknown in up to 50% of postmortem cases. Pathogenic mutations in genes encoding heart proteins are known to cause sudden cardiac death. Objective: The aim of our study was to ascertain whether genetic alterations could provide an explanation for sudden cardiac death in a juvenile cohort with no-conclusive cause of death after comprehensive autopsy. Methods: Twenty-nine cases <15 years showing no-conclusive cause of death after a comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 37 publications
2
30
0
Order By: Relevance
“…Post-mortem genetic testing by using specific gene panels or whole-exome sequencing (WES) represents an efficient tool to elucidate potential disease-causing mechanisms, which remained undetected during autopsy [8,12,13]. The exome represents approximately 1-2% of 4 the human genome, but it accounts for over 85% of all mutations that have been identified in Mendelian disorders [14].…”
Section: Introductionmentioning
confidence: 99%
“…Post-mortem genetic testing by using specific gene panels or whole-exome sequencing (WES) represents an efficient tool to elucidate potential disease-causing mechanisms, which remained undetected during autopsy [8,12,13]. The exome represents approximately 1-2% of 4 the human genome, but it accounts for over 85% of all mutations that have been identified in Mendelian disorders [14].…”
Section: Introductionmentioning
confidence: 99%
“…His medical history was unremarkable. The variant c.3457C > T (p.His1153Tyr) was previously reported in Table 4 List of all putatively pathogenic variants identified in the cohort within the 23 LQTS patients by Napolitano et al [30] and is reported in the Human Gene Mutation Database [31]. Case 5: Missense variants c.6007G > A (p.Asp2003Asn) in the SCN5A gene, previously undescribed, and c.5509G > A (p.Glu1837Lys) in the ANK2 gene, described by Mohler et al [32], were identified in a 20-year-old female who collapsed during psychiatric hospitalization, 2 weeks after her admission.…”
Section: Prioritization Process and Variant Pathogenicitymentioning
confidence: 99%
“…Until now, to our knowledge, only three studies have performed genetic testing using NGS technology on post-mortem samples of SUD. The study of Brion et al [21] used the SOLID TM system and the studies of Hertz et al [22] and Campuzano et al [23] used the MiSeq Illumina sequencer.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic analysis in post-mortem patients (also called molecular autopsy) may identify the genetic alteration responsible for an arrhythmogenic cardiac disease [5]. Current guidelines recommend performing the molecular autopsy in all these cases as a part of the comprehensive medico-legal investigation in SCD cases [6] but post-mortem genetic testing of the proband was reported in a low percentage of SCD cases with no structural alterations patients [7][8][9], mainly because forensic centers do not have the economic resources to perform genetic testing or do not collect samples due to currently legal restrictions involved with the sampling and storage of DNA [10].…”
Section: Introductionmentioning
confidence: 99%